Implementasi Layanan Kepegawaian Sistem Informasi Aplikasi Guru Surabaya (SIAGUS) di SMPN 13 Surabaya - Ammar A, Ahmad Faishal; Eprilianto, Deby Febrian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
SMPN 13 Surabaya is one of the schools under the supervision of the Surabaya City Education Office that has created an innovation aimed at facilitating educators in processing their rank promotion through an online system called Sistem Aplikasi Guru Surabaya (SIAGUS) or the Surabaya Teacher Application System. This study aims to describe and analyze the implementation of the online rank promotion system through the SIAGUS application at the Surabaya City Education Office. This research is a qualitative study using a descriptive approach. The focus of the research is the implementation of the SIAGUS application-based personnel service, based on the theory of Shams Rahman, Nahid Rashid, Aswini Yadlapalli, and Li Yiqun (2014), which consists of four factors: Institutional Factors, Resource-Related Factors, Access-Related Factors, and Legal/Regulatory Factors. Data collection techniques include interviews and document studies. Data analysis techniques consist of data collection, data reduction, data presentation, and drawing conclusions. The research data include primary data obtained through interviews and secondary data obtained through documentation, historical reports, and documents relevant to the research focus. The results of the study are as follows 1)Institutional factors, which include indicators of political commitment, leadership commitment, and organizational structure, are considered adequate in improving public service delivery due to full support from the agency leadership.2)Resource factors, consisting of human resources, technical capabilities, and financial indicators, are relatively good, although coordination with each school administrator is still needed.3)Access factors include Awareness, Education, and Capacity.4)Legal factors include regulatory frameworks, privacy, and security. The Surabaya City Education Office provides 24-hour service to teachers and education personnel through online platforms.